2022
DOI: 10.3389/fbioe.2022.998852
|View full text |Cite
|
Sign up to set email alerts
|

A versatile “3M” methodology to obtain superhydrophobic PDMS-based materials for antifouling applications

Abstract: Fouling, including inorganic, organic, bio-, and composite fouling seriously affects our daily life. To reduce these effects, antifouling strategies including fouling resistance, release, and degrading, have been proposed. Superhydrophobicity, the most widely used characteristic for antifouling that relies on surface wettability, can provide surfaces with antifouling abilities owing to its fouling resistance and/or release effects. PDMS shows valuable and wide applications in many fields, and due to the inhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 171 publications
0
5
0
Order By: Relevance
“…27 Hydroxyl-terminated polydimethylsiloxane (PDMS) is an important class of organosilicon compounds, characterized by a reactive hydroxyl group at the end of the main chain. 28 The synthesis of PDMS/polyurethane block copolymers using PDMS as soft chain segments can endow polyurethane with lower surface energy. [29][30][31] Imidazolium diols, because of their possession of two hydroxyl groups, are capable of forming stronger interactions with bacterial cell membranes, thereby enhancing the bacterial effect of imidazolium diols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Hydroxyl-terminated polydimethylsiloxane (PDMS) is an important class of organosilicon compounds, characterized by a reactive hydroxyl group at the end of the main chain. 28 The synthesis of PDMS/polyurethane block copolymers using PDMS as soft chain segments can endow polyurethane with lower surface energy. [29][30][31] Imidazolium diols, because of their possession of two hydroxyl groups, are capable of forming stronger interactions with bacterial cell membranes, thereby enhancing the bacterial effect of imidazolium diols.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyl‐terminated polydimethylsiloxane (PDMS) is an important class of organosilicon compounds, characterized by a reactive hydroxyl group at the end of the main chain 28 . The synthesis of PDMS/polyurethane block copolymers using PDMS as soft chain segments can endow polyurethane with lower surface energy 29–31 .…”
Section: Introductionmentioning
confidence: 99%
“…After years of exploration, people have been able to obtain superhydrophobic coatings through various methods. Common methods for preparing superhydrophobic materials include electrochemical deposition, , electrospinning, electrostatic spraying, CVD, LBL, , phase separation, photolithography, etc. However, most of these methods are not suitable for large-scale application in the corrosion protection industry due to cost reasons …”
Section: Introductionmentioning
confidence: 99%
“…Grasl et al (Grasl et al, 2021) tried to use thermoplastic polyurethane (PUR) and polylactic acid (PLLA) to prepare axial, circumferential, and randomly arranged fiber prostheses by electrospinning and found that different fiber structures had different mechanical properties, and even vascular prostheses with good mechanical properties comparable to those of natural blood vessels could be obtained by adjusting the fiber structure. A vascular graft requires good antiplatelet properties, and the materials must possess a good antifouling ability (Yang Lei et al, 2021;He et al, 2022). Therefore, materials are required to have proper hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%